Overview of Impacts of Climate Change and Adaptation in China's Agriculture - Jin-xia WANG; Ji-kun HUANG; Jun YANG (Journal of Integrative Agriculture, 2014)
The purpose of this paper is to document the likely impacts of climate change on China's agriculture and the current adaptation efforts made by government and farmers. The review of literature shows that climate change will have a significant impact on agriculture, primarily through its effect on crop yields. The extent of predicted impacts highly depends on the crop, the CO2 fertilization effect assumption and adaptation abilities. Market response to the production shocks resulting from climate change will lessen the impacts on agricultural production predicted by natural scientists. On adaptation, the government's major efforts have been in the developing new technologies, reforming extension system and enhancing institutional capacity. Farmers do adapt to climate change, but their adaptation measures cannot fully offset the negative impacts of climate change. The paper concludes and makes implications for future studies.